Comparison of diagnostic yield and safety of three endobronchial ultrasound-guided transbronchial biopsy techniques in diagnosing patients with mediastinal/hilar lymphadenopathy: a protocol of multicentre randomised trial in China - Deng, Mingming; Yang, Zhen; Zhong, Changhao; Zheng, Ziwen; Tong, Run; Zhou, Guowu; Li, Xuelian; Zhao, Ling; Herth, Felix; Hou, Gang (BMJ open, 2025)
Introduction Mediastinal and/or hilar lymphadenopathy (MHL) is increasingly identified owing to various underlying conditions. Minimally invasive biopsy techniques, including endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), transbronchial mediastinal cryobiopsy (TBMC) and transbronchial forceps biopsy (TBFB), are common diagnosis tools. However, their safety and diagnostic efficiency remain unclear. This trial aims to compare the diagnostic yield and safety of these three techniques. - Methods and analysis This study is a three-arm, parallel-design, randomised controlled trial involving 972 adult patients with MHL recruited from multiple medical centres. Participants will be randomly assigned to the EBUS-TBNA, TBMC via a tunnel or TBFB via a tunnel group. The primary outcome is diagnostic yield, and the secondary outcomes include diagnostic sensitivity, sample quality and procedure-related complications. Statistical analyses will be conducted using the appropriate methods. An independent sample χ² test will be used to test the differences in the diagnostic yield and incidence of procedure-related complications. - Ethics and dissemination Ethics approval was obtained from the China-Japan Friendship Hospital Ethics Committee (2022-KY-194).Written informed consent will be obtained from all patients or their guardians before their enrolment in the study. This study will be conducted per the principles established in the Declaration of Helsinki and the International Council for Harmonisation Guidelines for Good Clinical Practice.